Current-Controlled Current-Mode Quadrature Oscillator Using Translinear Current Conveyors - Montree Kumngern (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2019)
In this paper, a current-mode quadrature oscillator using second-generation current conveyors (CCIIs) is presented. The proposed oscillator consists of two CCIIs, two grounded capacitors and two grounded resistors. The circuit is suitable for integrated circuit implementation by using grounded capacitors. In addition, a new current-controlled current-mode quadrature oscillator using two current controlled second generation current conveyors (CCCIIs) and two grounded capacitors can be obtained by replacing CCIIs and resistors series at X terminals with CCCIIs. The condition of oscillation and frequency of oscillation can be orthogonally controlled. The frequency of oscillation can be controlled by grounded resistors and external bias currents. The proposed circuits have been simulated by SPICE simulations. The simulation results are confirmed the proposed theory.